Matrix-Assisted Laser Desorption/Ionization Matrices for Negative Mode Metabolomics. Issue 1 (February 2013) - Fagerer, Stephan R.; Nielsen, Simone; Ibáñez, Alfredo; Zenobi, Renato
Matrix-assisted laser desorption/ionization (MALDI) has been shown to be highly sensitive for analyzing low-mass compounds such as metabolites if the right matrix is used. 9-aminoacridine (9AA) is the most commonly employed matrix for negative mode MALDI-MS in metabolomics. However, matrix interferences and the strongly varying sensitivity for different metabolites make a search for alternative matrices desirable, in order to identify compounds with a different chemical background and/or favoring a different range of analytes. We tested the performance of a series of potential negative mode MALDI matrices with a mix of 29 metabolites containing amino acids, nucleotide phosphates and Krebs cycle intermediates. While ethacridine lactate was found to provide limits of detection (LODs) in the low femtomole range for nucleotide phosphates, amino acids and Krebs cycle intermediates in the low picomole range, 4-amino-2-methylquinoline showed LODs in the picomole range for most metabolites, but is capable of ionizing a broader range of analytes than both 9AA and ethacridine.